Religious Practice in the Digital Context: Addressing Radicalism on Social Media - Ahmad Baihaki; Burhanudin (al-Afkar, Journal For Islamic Studies, 2025)
This article examines how social media exacerbates religious radicalization and explores strategic measures to address it through a religious moderation approach. The phenomenon of religious radicalization on social media has become a complex and challenging global issue. Social media, as a digital interaction space, provides a significant opportunity for the spread of radical ideologies by leveraging platform algorithms to quickly reach a wider audience. The research adopts a qualitative approach based on literature studies, analyzing scholarly journals, reports, and related literature on digital radicalization. The findings reveal that radicalization on social media is often amplified by echo chambers, a lack of digital literacy, and algorithms that promote extreme content. The resulting impacts include social polarization, increased intolerance, and threats to societal diversity. However, the religious moderation approach offers an effective solution through the promotion of inclusive narratives, enhancement of digital literacy, and collaboration among various stakeholders, including governments, religious institutions, and technology platforms.